The Development of Microbiota and Metabolome in Small Intestine of Sika Deer (Cervus nippon) from Birth to Weaning - Li, Zhipeng; Wang, Xiaoxu; Zhang, Ting; Si, Huazhe; Nan, Weixiao; Xu, Chao; Guan, Leluo; Wright, André-Denis G.; Li, Guangyu (Frontiers in Microbiology, 2018)
The dense and diverse community of microorganisms inhibiting the gastrointestinal tract of ruminant animals plays critical roles in the metabolism and absorption of nutrients, and gut associated immune function. Understanding microbial colonization in the small intestine of new born ruminants is a vital first step towards manipulating gut function through interventions during early life to produce long-term positive effects on host productivity and health. Yet the knowledge of microbiota colonization and its induced metabolites of small intestine during early life is still limited. In the present study, we examined the microbiota and metabolome in the jejunum and ileum of neonatal sika deer (Cervus nippon) from birth to weaning at days 1, 42 and 70. The microbial data showed that diversity and richness were increased with age, but a highly individual variation was observed at day 1. Principal coordinate analysis revealed significant differences in microbial community composition across three time points in the jejunum and ileum. The abundance of Halomonas spp., Lactobacillus spp., Escherichia-Shigella and Bacteroides spp. tended to be decreased, while the proportion of Intestinibacter spp., Cellulosilyticum spp., Turicibacter spp., Clostridium sensu stricto 1 and Romboutsia spp. was significantly increased with age. For metabolome, metabolites separated from each other across the three time points in both jejunum and ileum. Moreover, the amounts of methionine, threonine, and putrescine were increased, while the amounts of myristic acid and pentadecanoic acid were decreased with age, respectively. The present study demonstrated that microbiota colonization and the metabolome becomes more developed in the small intestine with age. This may shed new light on the microbiota-metabolome-immune interaction during development.